Getting Down and Dirty with Impurity - Feder, Yitzhaq (The Biblical archaeology review, 2024)
Among the Hebrew Bible’s most obscure, perhaps even alien concepts is the notion of impurity. Modern readers may wonder what is to be gained from the detailed instructions pertaining to the pollution (ṭum’ah) caused by genital emissions, disease, corpses, and creepy-crawly creatures (Leviticus 11-15; Numbers 19). Why are we so reluctant to think about—let alone […]